AN OVERVIEW UNDERSTANDING ELDERLY AND PREELDERLY RESPONSES TO COVID-19 PREVENTION - Laksmita, Saka; Apriyanthi, Desak Putu Risky Vidika; Widayanti, Ni Putu (BioCONCETTA, 2023)
The elderly are vulnerable to infections around the world. This is because the elderly have a decreased immune system as they age. One of the infections circulating and endangering the elderly is Coronavirus disease 2019 (Covid-19). Covid-19 causes infections in the respiratory tract and even causes death. Although all ages have the risk of getting infected, people of advanced age have the risk of getting infected and becoming severe due to physiological changes along with the ageing process. This impact can affect their perceptions, attitudes and behaviours in dealing with the Covid-19 pandemic. This study used a quantitative survey design with cross-sectional. Data were collected from 170 respondents using Google which was disseminated via WhatsApp. The results showed that the majority of respondents had positive perceptions, good attitudes, and good behaviour with a percentage of 94.7%, 55.2%, and 50.5% respectively. The elderly and pre-elderly also need to increase their knowledge about COVID-19 prevention by accessing information provided by the government and related health workers.